De l’utopie socialiste au réalisme chrétien - Isabelle Richet (Transatlantica)
The New Deal was the first major reformist experiment in the history of the United States that was neither inspired nor supported by Protestantism. While a majority of Protestants and their clergy opposed Franklin Roosevelt from a conservative position, the theologian Reinhold Niebuhr developed a virulent left‑wing criticism of his policies, before finally rallying to his support at the end of the decade. Rejecting the idealism of the Social Gospel, unable to understand social relationships in term of class interests and power, Niebuhr used Marx’s analytical tools to develop a more realistic and efficient political approach. He saw the New Deal as a program aiming to save capitalism through state action, whereas the society based on social justice that he envisaged required the socialisation of the means of production which could be brought about only through social conflicts that may require the use of violence. However, under the influence of events in Europe after the rise of Hitler to power, he turned increasingly to theology. Inspired by the neo‑orthodoxy of Karl Barth and of his own brother, Richard Niebuhr, he reintroduced sin as the absolute limit of human action. Because of man’s sinful nature it was impossible to create a society based on justice and peace. His new theological absolutism led to political relativism. Indeed, realism now meant that in politics a Christian could only choose between the lesser of two evils. From this point of view the Democratic president and his preparedness campaign appeared as the only realistic choice in the context of the rise of fascism in Europe.